Quantification of Aeolian Bedform and Process Parameters in Thar Desert for Earth Surface Dynamics - Kar, Amal (Annals of Arid Zone, 2016)
Aeolian geomorphology, like other branches of geomorphological research, has undergone a gradual change over the past half a century, especially as digital revolution, access to various remote sensing products and sophistication in instruments for measurement have enabled perception and visualization of the bedforms and processes in such quantitative details that were never possible earlier. Small, compartmentalized, site-based studies devoted to one or two identified aspects are now getting replaced by wide-field, multi-disciplinary approaches for a holistic view of the issues involved in bedform-process interaction, and their relationship with the overall land surface dynamics. Relationships with large-scale atmospheric processes, studies on which were partly neglected during last few decades, are now being investigated in greater details, providing exciting new perspectives, or validating some old ideas. Since human beings have become a major driver of change in the sandy landscape, integrated analysis of bio-physical and social aspects are also getting due importance. Quantification of bedform and process parameters, as well as of a host of other linked fields, is a key to this new research. This article reviews and summarizes the aeolian research on Thar Desert in the light of the above developments. It also attempts to draw regional perspectives from the data generated by field-based research, and suggests a way forward. Key words: Granulometry, wind erosion, sand transport, dune movement, dune formation, dust emission, atmospheric boundary layer, remote sensing, GIS.